Abstract ISI 2007 Filipe+Braumann - Filipe, Patrícia A. (2008)
Scientific meeting: 56th Session of the International Statistical Institute, Lisboa Portugal, Aug 22-29, 2007. Oral communication on extension to several paths of estimation methods for stochastic differential equation models of individual animal growth (from birth to maturity).